(untitled) (Research, Society and Development, 2022)
Celiac disease is an autoimmune disease caused by the ingestion of gluten, a protein found in some cereals such as wheat and barley. Genetic and dietary aspects determine the degree of inflammation, resulting in important nutritional repercussions. Despite being underdiagnosed, its prevalence has increased in recent years due to greater knowledge and detection of the disease. The methodological approach of the research is qualitative and descriptive, as analyzed and interpreted in the scientific literature. The main objective of this research is to provide a greater degree of understanding regarding the pathology of the disease, clarifying the possible impacts on the health of a celiac individual. Based on this, it is considered of paramount importance to provide scientifically sound information to the interested public about the triggers and consequences of celiac disease. This review provides a comprehensive overview of celiac disease, particularly the clinical picture and diagnosis. The broad symptomatology is triggered by the consumption of gluten, which initiates an inflammatory process in the body of the carrier with a genetic predisposition to develop celiac disease. Systemic manifestations result from an autoimmune process and make early diagnosis difficult, impairing treatment adherence and, consequently, worsening prognosis. The diagnosis is confirmed through clinical data and laboratory tests.